Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Ask your questions and receive precise answers from experienced professionals across different disciplines. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
-3(3x+y=2) -> -9x-3y=-6
(-9x-3y=-6)+ (4x+3y=3) -> -5x=-3
x=3/5
then plug in the x into an equation to get y
y=1/5
(-9x-3y=-6)+ (4x+3y=3) -> -5x=-3
x=3/5
then plug in the x into an equation to get y
y=1/5
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.